Evaluation of mental disorders’ symptoms in students of Golestan University of Medical Sciences by SCL-90-R questionnaire - Taziki SA; Besharat S; Rabiee MR (مجله دانشگاه علوم پزشکی گرگان, 2005)
Background&Objective: Nowadays epidemiologic paterns of the diseases are verifying rapidly non-contagious diseases like mental disorders are replacing contagious one. Several people, unaware of their psychiatric problems seek medical advise and treating. College students are susceptible to mental disorders because of their conditions. This research was done to evaluate mental health state in students of Golestan University of Medical Sciences. Materials&Methods: 218 students of Golestan University took part in this research. SCL-90-R was the test for evaluation, after collecting the questionnaires and entering into SPSS-10 software, data were analyzed with chi-square and Fisher-exact test. Results: The momental prevalence was estimated 72%. 157 persons had disorder, at least in one dimension, and 16 persons (7.34%) had severe disorder at least in one. Marriage and psychosis, paranoid & anxiety had meaningful relations (P<0.05), residental site and paranoid had meaningful relations (P<0.05), higher levels of father’s education and interpersonal sensitivity had meaningful relation (P<0.05), Family history of mental disorders, moderate interest in education, field of study and phobia had meaningful relationships (P<0.05), females had higher scores in depression (P<0.05). Conclusion: According to this high prevelence of mental disorders it seems that mental health’s problem is critically high in this region, much more attention should be paid to prevent further complications.